Entrenamiento excéntrico como estrategia para mejorar el rendimiento en el cambio de dirección y el esprint en deportes de equipo: Una revisión sistemática - Gutiérrez-Hernández, S. J.; Pérez-Gómez, J.; Nobari, H.; Carlos-Vivas, J. (e-Motion. Revista de Educación, Motricidad e Investigación, 2020)
The present systematic review aimed to review the state of the literature in relation to studies that have analysed the effects of an eccentric training program on change of direction (COD) and sprint performance in team-sports, and to explore what might be the most appropriate characteristics to achieve the greatest adaptations on performance. A search was conducted in different databases: PubMed, Scopus, SPORTDiscus and Web of Science, including articles published up to 12 February 2020. A total of 11 studies met the eligibility criteria. The sample of all the included studies was composed of healthy physically active male team-sports subjects, over 16 years old, with different level of practice. Results show that eccentric training may be an appropriate strategy to improve COD and sprint performance in team-sports. Specifically, applying the eccentric method for at least 5 weeks, with a training frequency of 2-3 days per week, could lead to the greatest improvements in COD. However, the heterogeneity of the training protocols does not allow us to determine which volume of training would be most suitable to promote improvements in COD. Likewise, applying eccentric training for at least 5 weeks, with a frequency of 1-3 days per week, with a volume of 1-4 series of 5-16 repetitions could favour improvements in sprint performance